Leucemia mielóide aguda em crianças e adolescentes em instituições Brasileiras: realidade e desafios - de Melo Rodrigues, Ana Luiza; Lenzi, Luana; Lee-Jones, Lisa; Vieira Wanderley, Alayde; Marinho Da Silva, Ana Maria; Rocha De Carvalho, Cinthya; Teixeira Costa, Juliana; Galvão De Castro Junior, Cláudio; De Martino Lee, Maria Lucia; Mendes Lins, Mecneide; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2020)
Objective: To describe the outcome of acute myeloid leukemia (AML) among children treated in Brazilian institutions. Methods: A structured online questionnaire was sent to pediatric oncologists affiliated to the Brazilian Society of Pediatric Oncology. The physicians and institutions were unidentified. Results: One hundred and four pediatric oncologists in all Brazilian regions answered the questionnaire. The treatment-related mortality rate was reported to be higher than 30% by 29.8% of the participants. Difficulty in accessing the intensive care unit (ICU) was reported by 54.8%. About 85% had access to cytogenetics, 78% to molecular testing, 94% to the measurement of residual disease by flow cytometry. About 90% of participants reported access to HSCT, but 86% of them had difficulties in providing HSCT timely. About 95% of the respondents indicated the need to create a national treatment protocol, and 89.4% are willing to collaborate with a national study group. Conclusion: Our study demonstrated large gaps in the treatment of pediatric AML in Brazil. To improve outcome, a national protocol will have to consider the regional differences and adapt the management according to the local resources.